Modelling the browning of bread during baking - Purlis, Emmanuel (2009)
In this work, we study the development of browning at bread surface during baking. Computer vision is applied to follow the progress of browning at surface, while the variations of temperature and water activity are obtained by numerical simulation of a mathematical model previously validated. The formation of the bread crust is a complex process where temperature and water content change continuously during baking, making browning a non isothermal process occurring in a non ideal system. Minimum requirements for initiation of colour formation are temperature greater than 120 ºC and water activity less than 0.6. We apply a non isothermal kinetics approach to model the browning development at bread surface during baking, where the variation of local temperature and water activity is taken into account. The methodology presented here is suitable for modelling and predicting browning during baking; model parameters can be estimated by using a non ideal system closer to real processing conditions.